An exploratory study on the implementation of value management among engineering professionals in the Klang Valley / Fong Chong Yit - Fong, Chong Yit (2012)
It is foreseen by the Malaysian government that the implementation of Value Management through the 10th Malaysia Plan will be the guiding light towards better project management and delivery which will ensure greater values realisation to the general public. Engineering professionals being the front liners in supporting the implementation of public projects would be among the important stakeholders involved in the implementation of Value Management. A conceptual model is developed to determine the effects of resources, team dynamics and approach strategy towards the adoption of Value Management among engineering professionals in the Klang Valley with awareness acting as a moderator. Based on the responses from 105 participants, it was proposed that approach strategy is a significant predictor of the adoption of Value Management among engineering professionals in the Klang Valley while awareness moderates the effects of team dynamics towards the adoption of Value Management among engineering professionals in the Klang Valley. It is envisaged that the findings from this study will enable the stakeholders in promoting Value Management to strategise their efforts to ensure better acceptance of the notion of Value Management and subsequently ensure a more effective and efficient project management and delivery system.